Age at menopause and the correlates of natural menopause among urban and rural women in the southern Nigeria - Ikeanyi, Eugene M.; Ikobho, Ebenezer H. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Menopause, the point in a woman’s life when permanent cessation of cyclical menstruation occurs for a period of 12 months due to the loss of ovarian activity marking the end of reproductive lifespan and potential. Natural menopause is a physiological event, universal women phenomenon and irreversible part of the entire normal aging process. It brings the menopausal woman for preventive health care services due to its associated health implications. This study sought to investigate the age at menopause and its correlates in southern Nigerian women. Methods: A cross-sectional survey of datasets of women from two different communities attending annual religious conference was conducted using tested semi-structured researcher-administered questionnaire in 2019. Results: Data was analyzed on 152 participants from an urban and a rural communities. Mean chronological age was 58.8±8.8 years and parity was 6.4±2.2. Mean age at menopause was 50.0±4.6 years, median (IQR) 50.0 (47-53) and 49.2±4.7 versus 50.5±4.5 and median (IQR) 49.5 (46-51) and 50.5 (47-54) for urban and rural participants respectively. 1.3%, 9.2%, 69.7% and 19.7% were premature, early, normal and late onset menopause respectively. Risk of early onset menopause was insignificantly increased by higher education, social class, lower BMI and low parity. Forgetfulness (20.3%), irritability (19.5%), hot flushes (17.3%) and insomnia (16.5%) were the leading symptoms. Main complications were chronic hypertension 62 (40.8%), diabetes mellitus 12 (7.9%) and 4 (2.6%) recent fractures. Conclusions: Age at menopause was moderate, early menopause was rather high, programmed preventive healthcare services should address modifiable risk factors. Cancer screening services for late onset women is equally crucial.